BAŞKALE İLÇESİ'NİN (VAN) BEŞERİ VE İKTİSADİ COĞRAFYASI - TÜRKMEN, ERCAN (Fırat Üniveristesi, 2023)
İlçenin fiziki coğrafya özellikleri başka bir doktora tezinde çalışılmıştır. Bununla birlikte, ilçenin beşeri ve iktisadi özelliklerine yönelik kapsayıcı bir çalışmanın bulunmaması bu tezin çıkış noktası olmuştur. Araştırmada hem bölgesel hem de sistematik yaklaşım kullanılmıştır. Araştırma, literatür taraması, kurumlardan veri talepleri, saha çalışmaları, mülakat görüşmeleriyle yapılmıştır. Bu araştırma kapsamında, ilçenin özel konumunun, onun nüfus ve yerleşme özelliklerine nasıl yansıdığı öğrenilmek istenmiştir. Bunun yanında, ilçedeki iktisadi faaliyetlerin ve üretim şekillerinin belirlenmesi hedeflenmiştir. Bu çalışmada, sadece sorunlar tespit edilmemiş aynı zamanda çözüm önerileri oluşturmak amaçlanmıştır. İlçe nüfusunun 1935 yılından itibaren bir artış eğiliminde olduğu görülmüştür. Bu artış eğilimi, kırdan kente göçün yoğunlaştığı 1980'lerde de devam etmiş, 2011 yılında en yüksek seviyeye ulaşmıştır. Türkiye'nin birçok kırsal bölgesinde bu dönemlerde nüfus kaybı yaşanırken, ilçede nüfus artışı olmuştur. İlçe nüfusun diğer karakteristikleri bakımından da bölge ve ülkeyle farklılıklar göstermektedir. İlçede 66 köy, 66 mezra ve 4 mahalle bulunmaktadır. Genel olarak, dağlık sahalardaki köyler çok merkezli yerleşme özelliği gösterirken, plato alanlarındaki köyler ise tek merkezli yerleşme özelliği göstermektedir. İlçedeki yerleşmeler genel olarak toplu doku ve küme form özelliği göstermektedir. Dağların ve platoların geniş yer kaplaması, ilçede çayır ve mera alanlarının fazla olmasını sağlamıştır. Çayır ve mera alanlarının bolluğu da, ilçede hayvancılığın en önemli ekonomik faaliyet olmasını sağlamıştır. İlçe, özellikle küçükbaş hayvancılık yönünden sadece Van'da değil, Türkiye'de de önemli bir yere sahiptir. İlçedeki öncelikli ihtiyaçlar sulama kanalı, sulama göleti ve İran'la bir sınır kapısının açılması olarak belirlenmiştir. İlçedeki en önemli sorunlardan bir tanesi de, köylere ulaşım problemidir. Araştırma sahasında yapılan gözlemlerde ulaşım olanakları rahat ve iyi olan köylerin daha fazla gelişme gösterdiği, ancak ulaşım olanakları kötü olan köylerin ise geri kaldığı, hatta yok olma tehlikesi geçirdiği görülmüştür. Araştırma sahasında tarihi ve doğal turizm değerleri de bulunmaktadır. Ancak ulaşım imkanlarının yeterince iyi olmaması, turizm altyapısındaki eksiklikler ve ilçenin geçmişten beri terörle anılması, bu eserlerin yeterince ilgi görmesini engellemiştir.

The physical geography characteristics of the district have been studied in another doctoral thesis. Nevertheles, the lack of a comprehensive study on the human and economic characteristics of the district has been the starting point of this thesis. In the research, both systematic and regional approaches were utilized. The research was conducted through literature review, obtaining data from institutions, fieldwork, and survey-interviews. Within the scope of this research, it was desired to learn how the unique location of the district is reflected in its population and settlement characteristics. In addition, it is aimed to determine the economic activities and production methods in the district. In this study, not only the problems were identified, but also it was aimed to create solutions. In addition, it was thought that these solution proposals could be beneficial for similar rural areas It has been observed that the population of the district has been increasing since 1935. This increasing trend continued in the 1980s, when migration from rural to urban areas intensified, and reached its highest level in 2011. In many rural regions of Turkey, while the population declined during these periods, the population of the district increased. The district also differs from region and country in terms of other characteristics of the population. There are 66 villages, 66 hamlets, and 4 neighborhoods in the district. In general, villages in mountainous areas exhibit a multicenter settlement pattern, while villages in plateau areas display a monocenter settlement pattern. Settlements in the district generally exhibit the characteristics of a collective texture and a cluster form. The substantial presence of mountains and plateaus has resulted in the abundance of meadows and pasture areas across the district. Due to the abundance of meadows and pasture areas, livestock farming has become the most important economic activity in the district. The district holds great significance not only in Van but also throughout Turkey in terms of sheep and goat farming. The primary needs in the district have been determined as irrigation canal, irrigation reservoir, and the opening of a border gate with Iran. One of the major issues in the district is also the transportation problem to the villages. In the observations conducted in the research area, it has been observed that villages with easy and good transportation facilities show more development, while villages with poor transportation facilities do not develop and even face the risk of extinction. In the research area, there are historical and natural tourism assets. However, the lack of sufficient transportation facilities, deficiencies in tourism infrastructure, and the association of the district with terrorism in the past have hindered these attractions from receiving sufficient attention.
Human and economic geography of Baskale district (Van)
Keywords: Coğrafya